(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2021)
From the beginning of corona virus disease 19(COVID-19) pandemic, there has been concern how to protect vulnerable group like pregnant women from severe acute respiratory syndrome corona virus 2(SARS-CoV-2). Historically, pregnant women experiences increased mortality during any pandemic situation. Pregnant women show almost the similar clinical features as that of non-pregnant adults with COVID-19 infection. Different systematic reviews have begun to focus light on pregnancy outcomes in COVID-19 patients, but knowledge is very limited and still the basis is case series and individual experiences. Apart from the scientifically proven therapeutic options used in COVID-19 such as steroid, low molecular weight heparin, the role of convalescent plasma therapy (CPT) has never been evaluated. We present a case of a pregnant woman of 32 weeks of conception, treated with CPT with favourable outcome in a private hospital of Dhaka, Bangladesh. BSMMU J 2021; 14 (COVID -19 Supplement): 64-66